Dynamic thermal perception: A review and agenda for future experimental research. (November 2021) - Vellei, Marika; de Dear, Richard; Inard, Christian; Jay, Ollie
Abstract: Buildings could actively participate in the emerging smart electrical grid if they were able to incorporate dynamic modulations of indoor temperature set-points. But the mechanisms of dynamic thermal perception remain relatively poorly understood and we are still far from being able to design and control temperature fluctuations that would be comfortable for occupants. In this paper, we review the current state of knowledge on thermal comfort during non-steady state conditions. We especially focus on the psycho-physiological phenomena of thermal alliesthesia and thermal habituation, both of which are known to affect the dynamic thermal perception but have received scant attention in previous reviews and are yet to be fully characterized. By drawing from experimental literature (1960 through 2021) on thermal comfort under transient conditions and from recent neurophysiological evidence, we identify major knowledge gaps in the domain of dynamic thermal perception and set future research needs required to fill these gaps. Graphical abstract: Image 1 Highlights: Basics of thermal perception described. Phenomena of thermal alliesthesia and thermal habituation characterized. 46 dynamic thermal comfort experiments systematically reviewed. 10 open research questions on dynamic thermal perception identified. An agenda for future research prioritised.